Half-earth : our planet's fight for life - Wilson, Edward O. (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2016)
"In order to stave off the mass extinction of species, including our own, we must move swiftly to preserve the biodiversity of our planet, says Edward O. Wilson in his most impassioned book to date. Half-Earth argues that the situation facing us is too large to be solved piecemeal and proposes a solution commensurate with the magnitude of the problem: dedicate fully half the surface of the Earth to nature."--Amazon.